Penerapan Konsep Arsitektur Ekologi Dalam Desain Taman Reptil Di Kota Makassar - Burhanuddin, Muh. Luthfi; Amin, Burhanuddin; Attar, Muhammad (TIMPALAJA : Architecture Student Journals, 2022)
Reptiles are a class of vertebrate animals whose existence in nature is starting to be threatened because of their potential as a trading commodity for reptile animals, as pets, and the large number of wild reptiles being hunted for clothing and medicinal purposes. Humans have consumed reptile animals for various purposes so that they are threatened. Crocodile hunting takes its skin for raw materials for the bag, shoe industry, or several other industries. The aim of the research is to design a comfortable reptile park for administrators and visitors and how to design an artificial environment that is identical to the natural environment of reptiles. Descriptive method and design exploration with an ecological approach. It is hoped that the existence of this reptile park will be an entertainment place that is educational and barrier-free with facilities and parks so that the purpose of providing entertainment can still be fulfilled.